Filogenia molecular de Brachycephalus (Anura: Brachycephalidade) : A molecular phylogeny of Brachycephalus (Anura: Brachycephalidade) - Yamada, Juliana Yuri, 1989- (2017)
Orientadores: Sérgio Furtado dos Reis, Prianda Rios Laborda